2021
DOI: 10.1021/acsami.1c08285
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Supramolecular Hydrogel for Locoregional Immune Checkpoint Blockade and Enhanced Cancer Chemo-Immunotherapy

Abstract: Immunotherapy has revolutionized the therapeutic modalities of cancer treatment but is severely limited by a low objective response rate and the risk of immune-related side effects. Herein, an injectable supramolecular hydrogel is developed for local delivery of the D PPA-1 peptide (a D-peptide antagonist with a high binding affinity to programmed cell death-ligand 1 (PD-L1)) and doxorubicin (DOX). On the one hand, DOX could kill tumor cells directly and also induce immunogenic cell death to provoke the antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Some chemotherapeutic drugs also induce ICD, during which apoptotic cells release immune-related signals to initiate tumor-specific immune responses [ 167 , 168 ]. Synthetic polymeric scaffolds with prominent physiochemical performances have been developed for immunochemotherapy, lots of which have thermosensitive injectability and stimuli-responsive drug delivery [ 74 , 169 , 170 ]. Qiang Lv et al developed triblock-copolymer hydrogels from poly ( g -ethyl- l -glutamate)-poly (ethylene glycol)-poly ( g -ethyl- l -glutamate) (PELG-PEG-PELG) for local treatment of melanoma [ 171 ].…”
Section: Modern Immunotherapeutic Strategies Based On 3d Macroscale B...mentioning
confidence: 99%
“…Some chemotherapeutic drugs also induce ICD, during which apoptotic cells release immune-related signals to initiate tumor-specific immune responses [ 167 , 168 ]. Synthetic polymeric scaffolds with prominent physiochemical performances have been developed for immunochemotherapy, lots of which have thermosensitive injectability and stimuli-responsive drug delivery [ 74 , 169 , 170 ]. Qiang Lv et al developed triblock-copolymer hydrogels from poly ( g -ethyl- l -glutamate)-poly (ethylene glycol)-poly ( g -ethyl- l -glutamate) (PELG-PEG-PELG) for local treatment of melanoma [ 171 ].…”
Section: Modern Immunotherapeutic Strategies Based On 3d Macroscale B...mentioning
confidence: 99%
“…This immunoregulatory hydrogel system provides a new approach for improving the TME in immunosuppression and enhancing the effect of immunotherapy. In another study, Yang et al [ 65 ] developed a supramolecular hydrogel that encapsulated DOX and D PPA-1, a D-peptide antagonist with high affinity to PD-L1, for combined chemotherapy and immunotherapy. Drug-containing hydrogels injected into the tumor site can gradually release DOX and D PPA-1, which play a synergistic role in enhancing the infiltration of cytotoxic CD8+ T cells in tumors and inducing the secretion of TNF-α and IFN-Îł at the highest level.…”
Section: Injectable Hydrogel For Local Chemo-immunotherapy Combinationmentioning
confidence: 99%
“…It has been suggested that cryogels are more suitable for this application, as opposed to hydrogels, as a greater number of cells can be contained within the structure. With an exemption for injectable supramolecular hydrogel systems, which have been demonstrated to perform very well even after injection [74][75][76], hydrogels in general have been cited as being too brittle to enable injection [27]. Injectable cryogels have been investigated as scaffolds, for drug delivery, and for wound-healing applications.…”
Section: Injectable Cryogelsmentioning
confidence: 99%